HK-II expression and lactate production in PBMC-derived macrophages under inflammatory stimuli and hypoxia. - Kazunari Maekawa (14642343) (2025)
PBMC-derived macrophages were stimulated by TNFα (10 mg/mL) and INF-γ (20 ng/mL), hypoxia (1% O2), or IL-10 (10 ng/mL) for 4 h (A, HK-II mRNA expression) or 24 h (B, C, lactate production). Data are expressed as fold changes in comparison with the nonstimulated control. Kruskal–Wallis test was performed with Dunn’s multiple-comparison test (HK-II mRNA), and a one-way analysis of variance was performed with Sidak’s multiple-comparison test (lactate levels).